Smart IoT based Accident Monitoring and Rescue System - G., Sujithra; P., Kiruthika; S., Sibi Rathinam; A., Sruthi (Journal of ISMAC, 2024)
Today's drivers face a significant danger of vehicle accidents; hence, it is critical to devise innovative strategies to mitigate their impact and expedite emergency responses, especially considering the significant mortality rate. The proposed Internet-based Automatic Accident Detection and Rescue System (IoT-ADRS) optimizes accident detection and rescue operations by leveraging Internet of Things (IoT) technology. The framework combines several sensors, such as accelerometers, gyroscopes, ultrasonic sensors, GPS modules, and MQ3 sensors, to precisely identify accidents in real time. The Arduino microcontroller analyzes data from several sensors to identify accidents. The system employs GSM modules to transmit critical information, including the exact position and time of the event, to emergency services in real time upon detecting an accident. It examines key components and their connections to gather important data, quickly sound alarms, and manage resources efficiently. This comprehensive study shows that IoT-ADRS improves accident response protocols, saves lives, and reduces the severity of road injuries.
Keywords: Accident Detection; Alert System; Accelerometer; GPS; GSM; Vehicle Ad-hoc Network; Human Rescue System